A new dedicated clinic for HCWs' counseling and vaccination: experience of an academic hospital. (30th September 2020) - Malacarne, F; Brunelli, L; Miceli, S; Gallo, T; Petrin, G; Rosa, I; Gubian, F; Cocconi, R; Brusaferro, S
Abstract: Issue: Despite low healthcare workers (HCWs) vaccination coverage being a risk for hospital outbreaks, vaccine hesitancy is not unusual among HCWs. In Italy vaccinations are strongly recommended for HCWs, but there are few occasions for a dedicated counseling. Aim of the study is to evaluate the effectiveness of a new vaccination service in the academic hospital of Udine (northern Italy) in tackling vaccine hesitancy among HCWs. Description of the problem: Available data on HCWs specific antibody titers revealed that in high-risk units, 25% of HCWs were certainly unprotected for at least 1/6 of the vaccine preventable diseases (VPDs): measles, rubella, mumps, varicella, pertussis, hepatitis B; only varicella coverage reached the herd immunity target. Periodic occupational health visit was the only moment to screen for VPDs protection and suggest vaccination, but the following inconvenient procedure of HCWs contacting the vaccination office outside the hospital, often lead to delays or loss. In order to improve vaccination adherence, since June 2019 a dedicated clinic has been set up inside the hospital, making vaccination counseling and administration available every two weeks, with appointments directly given by the occupational doctor. Results: From June 2019 to February 2020, a total of 362 appointments were booked for the dedicated vaccination clinic, 69.7% of which actually took place as 252 HCWs actually accessed the service. Hours dedicated to the service activity were 76 hours, distributed over 19 days. Administered vaccination were 322, including 107 MMR (measles, rubella, mumps), 4 MMRV (MMR+varicella), 20 varicella, 64 hepatitis B, 127 DTPa (diphtheria, tetanus, pertussis). Lessons: Making the access to vaccination more convenient in term of service location within the hospital and giving the appointment when performing the occupational health visit seems to be helpful in filling the VPDs protection among HCWs gap. Key messages: Monitoring immunological status of HCWs and promoting vaccination at occupational health visit would sustain herd immunity protection for susceptible individuals in healthcare settings. The dedicated hospital vaccination clinic and the effective procedure of giving the appointment during the occupational health visit could be helpful in improving HCWs vaccine adherence.